Manipulation of pseudo-spin guiding and flat bands for topological edge states. Issue 21 (21st May 2019) - Jiang, Zhen; Gao, Yong-feng; He, Liu; Sun, Jia-ping; Song, He; Wang, Quan
Abstract : We manipulate pseudo-spin guiding and flat bands for topological edge states with elliptic cylinders based on silicon material. Abstract : Topological edge states and pseudo spins are promising paradigms to explore a new phase of matter in condensed matter physics. Here, we reveal the regulatory mechanism for guiding pseudo spin states along the interface between trivial and topological regions with elliptic cylinders made of conventional silicon material. A spin-guiding path introduced by an arrangement of elliptic cylinders exhibits high efficiency, large operation bandwidth and robustness to imperfections with tunable parameters. The pseudo spins of four types of silicon-based unit cells are measured, which may open exciting possibilities for unexpected topological properties such as flat bands. We manipulate a wide flat band with near-zero group velocities, which excites both pseudo spin up and down modes at the interface. The proposed concept might be implemented in photonic fabrication, facilitating potential applications for integrated optical devices.